Nature and Nurture: Effects of Affective Temperaments on Depressive Symptoms Are Markedly Modified by Stress Exposure - Gonda, Xenia; Eszlári, Nora; Sutori, Sara; Aspan, Nikoletta; Rihmer, Zoltan; Juhasz, Gabriella; Bagdy, Gyorgy (Frontiers in Psychiatry, 2020)
Lack of proper consideration of an the interaction between biological and environmental factors limits our understanding of the development of depression. Our cross-sectional study investigated how whether recent stress influences the effect of affective temperaments on depressive symptoms. Methods: 1015 general population subjects participants completed the Brief Symptom Inventory to capture depressive symptoms, the List of Threatening Experiences Questionnaire to assess recent stressors, and the Temperament Evaluation of Memphis Pisa, Paris and San Diego Autoquestionnaire to evaluate affective temperaments (TEMPS-A). Linear regression models were built to investigate the effect of temperament and stress on depression, temperament on stress, and the effect of temperament on depressive symptoms in different stress exposure groups. Results: Recent life events and anxious, depressive, cyclothymic and hyperthymic temperaments significantly predicted depressive symptoms, and cyclothymic, and hyperthymic temperaments significantly predicted recent life event exposure. While in case of mild stress, all affective temperaments except irritable predicted depression, in case of moderate exposure only the effect of depressive, cyclothymic and marginally hyperthymic temperament, while in the high exposure group only the effect of anxious temperament was significant. Limitations: All measures were based on self-report, and subjective impact of life events were not considered. This was a cross-sectional study with a correlational nature which does not allow for causative conclusions. Conclusions: The contribution of affective temperaments to depression is much higher compared to stress, and severity of exposure to life events influences the impact of affective temperaments on depressive symptoms pointing to divergent pathways of emotional reactivity mediating the effects of stress on depression which can be exploited for depression prevention and treatment.